Improvement of Awareness of Diabetes Mellitus Disease Risks and Self-Monitoring Motivation Through Blood Sugar Screening and Counseling for Dian Darat Village Community, Southeast Maluku - Meturan, Dessy Marselina; Ethica, Stalis Norma; Sukeksi, Andri (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
Diabetes Mellitus (DM) disease is among the top 10 causes of death in the world. It is a metabolic disease causing unusual high blood sugar level in the body. Fortunately, controlling risk factors through early detection can prevent the abnormality. Dian Darat is among villages in Southeast Maluku Regency, where DM screening is rarely carried due to its relatively remote location. This community activity aimed to provide DM disease education through blood sugar screening and counselling for village’s community. Methods included early detection of DM and counselling based on blood sugar level screening results supported by poster media. Screening test results showed that 9 out of 26 respondents (35%) had blood sugar level higher than normal. Based on results of pre- and post-test scores before and after the education, there was an increase in participants’ knowledge regarding DM disease by 62 %. (from average score of 56,15 ± 13,88 to 90,77 ± 9,77, n=26, p ≤ 0.01). Future community services are recommended on similar and more sustainable community service activities by cooperation with other relevant stakeholders to optimize results.